ORAL NARRATIVES AND SYMBOLIC EDUCATION: PEDAGOGICAL LESSONS FROM THE NON-HUMAN AMAZONIAN UNIVERSE (Interdisciplinary Studies Journal, 2024)
The aim of this paper is to understand how oral narratives related to the Boto teach and what they teach, considering the symbolic cultural and linguistic aspects. This is a qualitative study aimed at deepening our understanding of symbolic education in socio-communicative practices manifested in oral narratives related to the non-human entities that populate the Amazonian cosmological universe. The research questions are: Is there symbolic education through oral narratives? If so, in what way is this education presented or personified through the Boto? The study points out that the relationship between Symbolic Education and its students depends not just on the passage of the symbol, but on a whole cultural set that is built up daily, spontaneously, collectively, and sensitively in the various socio-communicative interactions. It is thus a collective education, built by everyone in the community who shares the same cultural and symbolic context.
Keywords: Oral narrative; Boto; Amazonian imaginary; Symbolic Education